Analysis of Caesarean Section Rate in a Hospital of Central India: According to Robson’s 10-Group Classification - Amruta Choudhary (Ladke)1 , Kshipra Bhangadia2 , Deepti Shrivastav3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Caesarean section is most common surgery performed worldwide, but increasing rate ofcaesarean birth has become an international concern of public health. According to WHO (World HealthOrganisation), rate of caesarean section should not be more than 15%.Aims and Objective: The main aim of this study was to classify the caesarean section according to Robsons’sciteria and to identify the rising causes of caesarean section in our scenario.Material and Method: This was a cross sectional observational study and data was collected over a periodof six months from every single patient, who underwent caesarean section in our hospital.Results: During the study period, total number of deliveries in this hospital was 519, out of which there were300 caesarean section, thus, we have 57.80% rate of caesarean section. Maximum rate of caesarean sectionwas in group 5 i.e. Multiparous with prior caesarean section, singleton, cephalic, ?37 weeks followed bygroup 2 i.e. Nulliparous, singleton, cephalic, ?37 weeks, induced labour or caesarean section before labour.Conclusions: This attempt of classifying the caesarean section by Robson’s criteria helped to audit andidentify the problem and to think about modifying the hospital protocols for reduction of rate of caesareansection.